The role of the financial accounting system in enhancing governance in the commercial corporate sector - Mekherbeche, Madiha (The International tax journal, 2025)
This study seeks to emphasize the importance of the financial accounting system in reinforcing and operationalizing governance principles within the commercial corporate sector. The financial accounting system is regarded as a critical instrument for restoring confidence in financial statements by improving their quality and reliability. It plays a vital role in facilitating the implementation of governance by enhancing transparency and credibility in financial operations. Moreover, the study examines the role of Algerian legislation in promoting these principles through relevant agreements and statutory provisions, thereby reinforcing corporate governance and contributing to institutional stability.